Begrepp i bur: Om kulturbruk och kulturbråk - Ekström, Simon (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2010)
The Swedish debate concerning honour killings has largely revolved around the concept of "culture" — or more specifically, it has revolved around the ways in which different writers have criticized some other debaters for misusing the concept. Hence, this debate sheds light on how the concept of culture has come to occupy a position in something one might call a linguistic quarantine. Cultural explanations are often considered an issue which must be handled with great caution in order not to explode into cultural racism, or to an undesired exaggeration of cultural difference. Moreover, the most serious objections against the concept of culture seem to occur in the very field which the concept has traditionally been regarded as most suitable for. Recent controversies around phenomena such as honour killings, structural discrimination and cultural racism reveals that it first and foremost is in relation to the "exotic other" that cultural explanations nowadays are becoming questioned. On the other hand, few debaters and researchers are ready to seriously do away with a concept they continue to understand as applicable for their own analyses. The aim of this article is, therefore, to highlight some of the critical arguments in this debate, so as to discuss the ambivalences that distinguish contemporary public disputes about culture and cultural explanations.